Unapproved Combination Therapy of Doxycycline and Ivermectin in Covid-19 Pandemic, an Opportunistic Chance of Self-medication: A Case Report - Bano, Gulnaz; Sharma, Abhishek (Journal of Pharmacy Practice and Community Medicine)
To date, no standard drug therapy has proven effective to counter COVID-19 disease. There are only hit and trial based on assumptions and weak evidence that are directing prescribing practices for asymptomatic to symptomatic and serious cases of COVID-19. ICMR being the apex body, responsible for framing the guidelines for the management of disease in India has not yet approved the use of combination doxycycline and ivermectin in the prophylaxis or treatment of Covid-19 cases but being used in the treatment of COVID-19 infection. Their adverse drug reactions individually are well known among scientific community. Doxycycline ADRs range from gastrointestinal, urogenital, neuropsychiatric, respiratory, nervous system to skin and appendages. We have reported a case of doxycycline induced drug allergy (rashes) all over the trunk and legs as a result of self-medication. The event happened after a female patient had complaints of persistent fever and weakness consumed doxycycline and ivermectin on her friend’s advice and developed rashes on her trunk and legs. The above ADE is very mild but alarming for the medical fraternity that warrants strict compliance with the electronic/text/online prescription. The usage of doxycycline and ivermectin in the treatment of COVID-19 disease, as an indication of treatment should not be considered prior to any concrete evidence or issuance of treatment, guidelines by the apex body in India.
Keywords: COVID-19; Self-medication; ADRs; ADE; ICMR; Doxycycline; Ivermectin; Rashes